High spatial resolution of distribution and interconnections between Fe‐ and N‐redox processes in profundal lake sediments. (15th August 2014) - Melton, Emily D.; Stief, Peter; Behrens, Sebastian; Kappler, Andreas; Schmidt, Caroline
Summary The Fe and N biogeochemical cycles play key roles in freshwater environments. We aimed to determine the spatial positioning and interconnections of the N and Fe cycles in profundal lake sediments. The gradients of O2, NO3−, NH4+, pH, Eh, Fe(II) and Fe(III) were determined and the distribution of microorganisms was assessed by most probable numbers and quantitative polymerase chain reaction. The redox zones could be divided into an oxic zone (0–8 mm), where microaerophiles (Gallionellaceae) were most abundant at a depth of 7 mm. This was followed by a denitrification zone (6–12 mm), where NO3−‐dependent Fe(II) oxidizers and organoheterotrophic denitrifiers both reduce nitrate. Lastly, an iron redox transition zone was identified at 12.5–22.5 mm. Fe(III) was most abundant above this zone while Fe(II) was most abundant beneath. The high abundance of poorly crystalline iron suggested iron cycling. The Fe and N cycles are biologically connected through nitrate‐reducing Fe(II) oxidizers and chemically by NOx− species formed during denitrification, which can chemically oxidize Fe(II). This study combines high resolution chemical, molecular and microbiological data to pinpoint sedimentary redox zones in which Fe is cycled between Fe(II) and Fe(III) and where Fe and N‐redox processes interact.